A novel AlGaN/GaN multiple aperture vertical high electron mobility transistor with silicon oxide current blocking layer. (August 2015) - Shrestha, Niraj Man; Wang, Yuen Yee; Li, Yiming; Chang, Edward Yi
Abstract: In this work, a new AlGaN/GaN vertical high electron mobility transistor (HEMT) with silicon oxide (SiO2 ) current blocking layer (CBL) is designed and studied numerically for high-power devices. To overcome the excessive vertical leakage through CBL layer in conventional p-GaN CBL vertical HEMT, large band-gap material, SiO2 is, for the first time, introduced as a CBL material. The band-gap of SiO2 leads to a large barrier which can effectively suppress the vertical leakage even at high drain bias and enhance the breakdown voltage to 1270 V (154% enhancement compared with the conventional p-GaN CBL vertical HEMT). In addition, a device with four parallel apertures is proposed to reduce the aperture resistance, where the total aperture thickness is equal to the aperture thickness of the conventional one. Therefore, the drain current is increased. We not only focus on the vertical leakage control, but also, on the drain current boost (7% improvement). Highlights: Silicon oxide material for current blocking layer in vertical HEMTs. Regrowth by pendeo epitaxial method. Vertical leakage is effectively decreased. Breakdown voltage is sufficiently high. Multiple apertures can reduce on-state resistance and increase drain current.